United States : Publication of Financial Sector Assessment Program Documentation; Technical Note on Basel II Implementation Preparedness in the United States. (IMF Staff Country Reports; Country Report, 2010)
The key findings of the United States's Basel II Implementation Preparedness are discussed. Certain policy choices that the authorities have made or may make related to allowing banks to choose the capital regime that applies to them may open up arbitrage possibilities that the authorities need to take into account in the future. Each agency has a well-articulated overall Basel II strategy that has been disseminated to appropriate supervisory staff and communicated to relevant banking organizations.